2008
DOI: 10.1192/bjp.bp.107.039180
|View full text |Cite
|
Sign up to set email alerts
|

Major depression, 5HTTLPR genotype, suicide and antidepressant influences on thalamic volume

Abstract: The 5HTTLPR genetic variation may affect behaviour and psychiatric conditions, in part, by altering the anatomy of the thalamus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 27 publications
5
31
2
2
Order By: Relevance
“…42 Previous research has shown that functional and histological abnormalities in the thalamus are involved in the pathophysiology of depression and suicidal behaviours. 43 The present study also showed that depressed patients without a history of suicidal behaviour had decreased fibres in frontothalamic pathways passing to specific prefrontal regions and to the thalamus relative to healthy controls. In patients with a history of suicide attempts, we observed a more severe reduction in these pathways in the OFC and thalamus than in depressed patients without a history of suicide attempts.…”
Section: 38supporting
confidence: 49%
“…42 Previous research has shown that functional and histological abnormalities in the thalamus are involved in the pathophysiology of depression and suicidal behaviours. 43 The present study also showed that depressed patients without a history of suicidal behaviour had decreased fibres in frontothalamic pathways passing to specific prefrontal regions and to the thalamus relative to healthy controls. In patients with a history of suicide attempts, we observed a more severe reduction in these pathways in the OFC and thalamus than in depressed patients without a history of suicide attempts.…”
Section: 38supporting
confidence: 49%
“…Although reduced thalamic volume was reported in adult women with MDD (Kim et al 2008), this may be the first report of such deficits during early-onset depression. Interestingly, a postmortem study in depressed adults reported an increase in the number of neurons in the mediodorsal and anteroventral/anteromedial nuclei of the thalamus that connect subcortical limbic system structures (such as the amygdala) with the prefrontal and cingulate cortices (Young et al 2004). Furthermore, an association between history of antidepressant use and reduction in the volume of various thalamic nuclei in depressed subjects (Young et al 2008) suggests a potential antidepressant effect on the thalamus.…”
Section: Shad Et Almentioning
confidence: 99%
“…Interestingly, a postmortem study in depressed adults reported an increase in the number of neurons in the mediodorsal and anteroventral/anteromedial nuclei of the thalamus that connect subcortical limbic system structures (such as the amygdala) with the prefrontal and cingulate cortices (Young et al 2004). Furthermore, an association between history of antidepressant use and reduction in the volume of various thalamic nuclei in depressed subjects (Young et al 2008) suggests a potential antidepressant effect on the thalamus. In the current study, most of the depressed participants were never exposed to psychotropic agents and in the small subgroup (18%) that had ever been exposed to antidepressant agents, the duration of exposure was relatively brief ( < 2 months) and also not in close proximity to the MRI study.…”
Section: Shad Et Almentioning
confidence: 99%
“…Likewise, we exclude cell number estimates based upon cell counts without guard zones needed to eliminate the confounding of neurons lost when tissue sections are cut. It is important to note that some of the included studies provided very limited details regarding the stereological methods employed; however, these (Mileaf and Byne, 2012; Young et al, 2008) were included as the terminology used suggested that they met our criteria.…”
Section: Introductionmentioning
confidence: 99%